Seed bank from different successional stages in the Fonte Grande State Park, ES, Brazil - Tatiana Pizetta Dias; Larissa Regina Topanotti; Fernando Campanhã Bechara; Luiz Fernando Silva Magnago; Izaclaudia Santana da Cruz; Marcelo Simonelli (Acta Biológica Catarinense, 2021)
This investigation aimed to determine the density of viable seeds and to compare the floristic composition of the seed bank from different forest successional stages – initial and intermediate – at the Fonte Grande State Park, Vitória, state of Espírito Santo, Brazil. Samples of 15 × 15 × 5 cm of soil and litter were collected, in 15 points, in each successional stage. After five months cultivating these samples in a greenhouse for botanical identification, the soil showed higher seedlings density and richness of species than the litter. A total of 1,414 seedlings was quantified: 78.3% of the individuals were in the initial stage (µ = 3,280 seedlings.m-2), and 21.7% were in the intermediate stage (µ = 910 seedlings.m-2). The richness of species between the stages was similar (53.2%), 33 species occurring in both areas. The predominant life form in both stages was herbaceous, though the intermediate stage presented more trees. These patterns indicate an early phase of the intermediate stage, which, over the successional time, will probably advance to an old-growth forest.